Eladio Dieste - Pedreschi, Remo (Engineer's contribution to contemporary architecture., 2000)
This volume reviews the work of Eladio Dieste. It discusses Dieste's own approach to his work, using many examples, and explores the interrelationship between the structural form and architecture of the buildings.